Formulasi Sediaan Krim Antioksidan Ekstrak Buah Terap (Artocarpus odoratissimus Blanco) dengan Basis Virgin Coconut Oil (VCO) - Heriani Rani; Irma Novrianti (Politeknik Kaltara, 2023)
Antioxidants are compounds that can counteract the negative effects of oxidants from other molecules which are one of the causes of premature aging. Terap fruit (Artocarpus odoratissimus Blanco) is a type of plant that contains antioxidant compounds. This research aimed to make a cream preparation with extracts from therapeutic fruit using a VCO base. The terap fruit simplicia powder was macerated using 96% ethanol solvent for three days to obtain a liquid extract which was then concentrated by evaporation over a water bath. The formula was made with variations in extract concentration, namely 0.1%, 1%, and 10% with observations for 4 days including organoleptic observations, homogeneity, pH of the preparation, stability of the cream, and determining the type of emulsion. The results of the research showed that the three creams had good characteristics during the storage period, especially in formula 1 from the 0.1 extract organoleptic test which had very good results, for homogeneity the three formulas had good homogeneity during the storage period, and irritation results for all formulas showed that the preparation is not irritating to the skin.